Intricate balance of dually-localized catalase modulates infectivity of Leptomonas seymouri (Kinetoplastea: Trypanosomatidae) - Chmelová, Ľubomíra; Kraeva, Natalya; Saura, Andreu; Krayzel, Adam; Vieira, Cecilia Stahl; Ferreira, Tainá Neves; Soares, Rodrigo Pedro; Bučková, Barbora; Galan, Arnau; Horáková, Eva; Vojtková, Barbora; Sádlová, Jovana; et al. (International journal for parasitology, 2024)
Nearly all aerobic organisms are equipped with catalases, powerful enzymes scavenging hydrogen peroxide and facilitating defense against harmful reactive oxygen species. In trypanosomatids, this enzyme was not present in the common ancestor, yet it had been independently acquired by different lineages of monoxenous trypanosomatids from different bacteria at least three times. This observation posited an obvious question: why was catalase so "sought after" if many trypanosomatid groups do just fine without it? In this work, we analyzed subcellular localization and function of catalase in Leptomonas seymouri. We demonstrated that this enzyme is present in the cytoplasm and a subset of glycosomes, and that its cytoplasmic retention is H2O2-dependent. The ablation of catalase in this parasite is not detrimental in vivo, while its overexpression resulted in a substantially higher parasite load in the experimental infection of Dysdercus peruvianus. We propose that the capacity of studied flagellates to modulate the catalase activity in the midgut of its insect host facilitates their development and protects them from oxidative damage at elevated temperatures.
Keywords: katalasa; Hydrogen Peroxide; Animals; Catalase; Trypanosomatids; Trypanosomatina; Cytoplasm; Microbodies; Hydrogen peroxide; mikrotělíska; peroxid vodíku; cytoplazma; zvířata